A LINGUISTIC ANALYSIS OF GRIEF, METAPHOR, AND IDENTITY IN THE LYRICS OF NICKI MINAJ - AHABUE, Amen Onome (International Journal of Arts, Languages, Linguistics and Literary Studies, 2025)
This study investigates how language in popular music functions as a performative tool for expressing grief and constructing identity. Drawing on Conceptual Metaphor Theory (CMT) and the Sociolinguistics of Identity, the paper conducts a detailed linguistic analysis of four autobiographical songs by Nicki Minaj: “Autobiography,” “All Things Go,” “Last Time I Saw You,” and “Are You Gone Already.” The research explores how metaphor, deixis, evaluative language, and narrative stance reveal the singer’s evolving affective and social self. Through CMT, recurring metaphors such as Life Is a Journey, Grief Is a Weight, And Time is a Thief are decoded to show how abstract emotional states are conceptualized through embodied and experiential language. From a sociolinguistic perspective, the analysis demonstrates how Minaj positions herself within multiple shifting identities—artist, daughter, mother, and sister—while negotiating trauma, loss, and fame. The findings reveal that language in Minaj’s lyrics operates not only as aesthetic expression but also as an index of emotional labour and identity performance. This paper contributes to growing scholarship at the intersection of linguistics, music, and affect by demonstrating how autobiographical rap lyrics serve as a meaningful site for identity construction and emotional narration. It argues for the inclusion of hip-hop texts as valid and necessary material for linguistic analysis, especially in the African American and global diasporic cultural context.